A UV-LED excited photoinitiator with low toxicity and low migration for photocurable inks. (April 2022) - Ren, Xiaozhen; Liu, Wenkai; Yao, Qichao; Wang, Siqi; Liu, Weijian; Gu, Hua; Wang, Dongping; Fan, Jiangli; Peng, Xiaojun
Abstract: With the improvement of public's environmental protection awareness, the market share of LED in the photocuring field is also expanding rapidly, so it is necessary to develop matching photoinitiators. Here, we prepared a molecule (ND-1 ) possessing both co-initiating and polymerizable groups, and it exhibits a good initiation effect on acrylate monomers under UV-LED irradiation. The double bond conversion rate reaches up to 80% especially for tripropylene glycol diacrylate (TPGDA). Due to excellent photocuring effect of ND-1, it can initiate monomer polymerization in the presence of color paste and was successfully applied to photocurable inks. In addition, ND-1 exhibits low migration and low toxicity, which is very important to promote the application of packaging with photocurable inks in the food, medical, personal care and tobacco fields. Finally, the photoinitiation mechanism of ND-1 was explored. The free radicals not only come from the cleavage of C─O bond, but also intermolecular hydrogen abstraction. Highlights: A novel photoinitiator ND-1 with low toxicity and low-migration was synthesized. ND-1 can initiate photopolymerization of acrylate monomers under UV-LED irradiation. The free radicals are produced through ND-1 homolysis and intermolecular hydrogen abstraction. ND-1 has been successfully applied to photocurable inks.